2018
DOI: 10.1155/2018/9492453
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Detoxification on Sleep: How Does Sleep Quality Change during Qualified Detoxification Treatment?

Abstract: Aims. Sleep disturbances are common in addiction and withdrawal. This study examined the course of sleep quality in a population of alcohol dependent patients during qualified detoxification treatment in a psychiatric hospital. Methods. The Pittsburgh Sleep Quality Index (PSQI) was administered to 77 electively admitted alcohol dependent patients hospitalized for qualified detoxification treatment. Sleep quality was measured at admission and at discharge. Results. The prevalence of bad sleep as measured by a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Six studies reported outcomes related to sleep during withdrawal treatment. Three studies used Actigraphy, an objective measure [ 37 , 44 , 55 ], two studies used self‐report measures, such as the Pittsburgh Sleep Quality Index [ 89 , 96 ], and two used the Sleep‐Related Behaviours Questionnaire [ 44 , 89 ]. Another eight separate studies used eight different measures, including beliefs and attitudes about sleep, hours of sleep and other sleep details (e.g., onset latency, wake time, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported outcomes related to sleep during withdrawal treatment. Three studies used Actigraphy, an objective measure [ 37 , 44 , 55 ], two studies used self‐report measures, such as the Pittsburgh Sleep Quality Index [ 89 , 96 ], and two used the Sleep‐Related Behaviours Questionnaire [ 44 , 89 ]. Another eight separate studies used eight different measures, including beliefs and attitudes about sleep, hours of sleep and other sleep details (e.g., onset latency, wake time, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…15 In a recent study of 77 patients with alcohol dependence electively admitted to a hospital for detoxification, 70.1% had PSQI scores greater than five at admission which fell to 59.7% at discharge. 3 From the above analyses, it is clear that the incidence of insomnia associated with alcohol cessation both during and after detoxification is high.…”
Section: Prevalence Of Iaacmentioning
confidence: 98%
“…Insomnia commonly occurs in the acute withdrawal phase (1 to 2 weeks) and early recovery phase (2 to 8 weeks after detoxification). In the acute withdrawal phase, insomnia symptoms are variable and can improve over the detoxification period, 3 yet may continue into the sustained recovery phase (3 or more months after the detoxification phase). During the sustained recovery phase, sleep‐related disturbances can continue for up to 3 years 4–6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensuring the sleep improvement during addiction treatment is important as quality control of detoxification, and prevention for relapse (10, 32). Normalized sleep pattern and circadian rhythm could increase the resilience to addiction (33).…”
Section: Rtms For Sleep Disorder In Addictionmentioning
confidence: 99%